Synergistic modification by mercapto hyperbranched polysiloxane and functionalized graphene oxide on the surface of aramid fiber. (November 2020) - Yang, Xuan; Tu, Qunzhang; Shen, Xinmin; Pan, Ming; Jiang, Chengming; Lai, Xitao; Xue, Jinhong
Abstract: With the purpose of improving the interfacial properties of aramid fibers reinforced rubber composites and enhancing the tensile strength of aramid fibers simultaneously, mercapto hyperbranched polysiloxane (HPSi) and functionalized graphene oxide (GO) were used to modify the surface of aramid fibers. Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and other characterization methods were performed to confirm the process of synergistic modification. Judging from the results of mechanical property tests, it could be acquired that the tensile strength of modified aramid fiber was increased by 16.8%, which could be ascribed to the wrapping effect of GO sheets. The interfacial properties were assessed by the pull-out tests of composites, and the results showed that the maximum pull-out force after synergistic surface modification was increased by 99.3%, which could be mainly related to additive reaction between double bonds and mercapto groups and the promotion of surface energy. More critically, during pull-out test, aramid fiber bundles might bring a part of shear stress into the grafted GO sheets, namely, GO sheets could convert fracture energy into interfacial energy, which would improve interfacial properties dramatically. Highlights: Mercapto HPSi and GO were used for surface modification of aramid fiber. The statistical average single strength of modified aramid fiber was increased by 16.8%. The bonding strength of modified aramid fiber/rubber was increased by 99.3%. The wrapped HPSi/GO can share fiber tensile stress and interfacial fracture stress. This modification strategy has a universality for other high-performance fibers.